THE NEW PARADIGM: Procedural Sedation in the Covid-19 Era - Romano Ribeiro, Carolina (2021)
The SARS-CoV-2 pandemic has dramatically changed our clinical practice. Although elective procedures were initially postponed1, medical departments had to create conditions for a safe return to routine activity as well as increasing the safety of urgent procedures. These images refer to a left atrial appendage (LAA) closure with a WACTHMAN FLX device, in a 76-year-old man with atrial fibrillation and cerebrovascular disease (and contraindication to anticoagulation/high bleeding risk). It was performed with transesophageal echocardiography under deep sedation and spontaneous ventilation, similar to our preferred anesthetic technique for this type of patients and procedure. Strategies to minimize virus dispersion, as personal protective equipment, low flow oxygen therapy and plastic boxes, have been described to minimize virus dispersion.2 Although in our institution, barrier boxes have been used in the operating room for endotracheal intubation, they do not have compatible configuration for cardiac catheterization lab. Thus in order to carry out these procedures, an arch with plastic protection was specifically created to be placed around the patient’s airway, providing maximal protection to the health care team.   This device allows the procedures and projections to be carried out safely without interfering with the anesthetic plan.   Ongoing Heart Team activity and communication are vital to provide the best outcome.1